2011
DOI: 10.1186/1475-2891-10-111
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between anthropometric variables and nutrient intake in apparently healthy male elderly individuals: A study from Pakistan

Abstract: BackgroundThe elderly population is increasing worldwide, which warrants their nutritional status assessment more important. The present study was undertaken to establish the nutritional status of the least-studied elderly population in Pakistan.MethodsThis was a cross-sectional study with a sample of 526 generally healthy free-living elderly men (mean age: 68.9 yr; range: 50-98 yr) from Peshawar, Pakistan. Anthropometric measurements (weight, height, WC) were measured and BMI and WHR were calculated from thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
1
15
0
2
Order By: Relevance
“…In analogy to older Western (Swedish) populations, these values would put many Pakistani elderly in the IRP group which is found in a minority of people over 65 in Sweden, and which is known to become predictive of incipient mortality from 85 years of age . The definition of "aged" in Pakistan is considerably lower than 65 year (Alam et al 2011), and in parallel with this, possibly the IRP also occurs at an earlier age. Whether this is indeed predictive of mortality in this Pakistani population remains to be established in longitudinal follow-up studies.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In analogy to older Western (Swedish) populations, these values would put many Pakistani elderly in the IRP group which is found in a minority of people over 65 in Sweden, and which is known to become predictive of incipient mortality from 85 years of age . The definition of "aged" in Pakistan is considerably lower than 65 year (Alam et al 2011), and in parallel with this, possibly the IRP also occurs at an earlier age. Whether this is indeed predictive of mortality in this Pakistani population remains to be established in longitudinal follow-up studies.…”
Section: Discussionmentioning
confidence: 96%
“…Potential subjects expressing interest in blood donation were first screened by obtaining a verbal medical history to rule out any health conditions or medication use that could affect immune responses. For the current study, we used a subsample from our previous study conducted in Peshawar, Pakistan (Alam et al 2011). We selected a convenience sample of 50 families and from each family we selected one young and one elderly subject fulfilling the inclusion criteria.…”
Section: Study Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shukla et al (9) in their study on urban Indian adults found that 24-36% and 24-48% of males and females aged 65years and above were underweight. In a recent study it has been reported that 11% of healthy elderly Pakistani men are underweight (18).With respect to the prevalence of overweight and obesity, strict comparisons across Asian studies are not possible due the differences in BMI cut-offs that have been used to define these two entities. According to the BMI cutoffs used in this study, 13 and 12% of the males were overweight and obese respectively while the figures for the females were 18 and 23% respectively.…”
Section: Resultsmentioning
confidence: 99%